1958
DOI: 10.3109/00016485809134738
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intense Sound on the Non-Auditory Labyrinth

Abstract: Two groups of guinea pigs were stimulated by a noise of 136 db and 150 db above 0.0002 dyne/cm' respectively, and were examined histologically for disturbance of the vestibular labyrinth. The saccule was found to be the locus of damage for these high level sounds. Other structures of the vestibule remained normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

1960
1960
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 17 publications
1
25
0
2
Order By: Relevance
“…With the intensity of more than 130 dBSPL, mechanical injury to the inner ear is inevitable, and individual variation is minimal, leading to irreversible sensorineural HL. At an intensity of 136 to 150 dBSPL to guinea pigs for 20 min, damages to the otolithic membrane and saccular collapse were observed (20). Therefore, the greater the noise intensity, the severer damage on the cochlea and saccule can be anticipated, consistent with our results that those with absent or delayed VEMPs after acoustic trauma had their HL remained unchanged.…”
Section: Discussionsupporting
confidence: 87%
“…With the intensity of more than 130 dBSPL, mechanical injury to the inner ear is inevitable, and individual variation is minimal, leading to irreversible sensorineural HL. At an intensity of 136 to 150 dBSPL to guinea pigs for 20 min, damages to the otolithic membrane and saccular collapse were observed (20). Therefore, the greater the noise intensity, the severer damage on the cochlea and saccule can be anticipated, consistent with our results that those with absent or delayed VEMPs after acoustic trauma had their HL remained unchanged.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, ear plugs combined with earmuffs may be insufficient to protect the saccule from long term gunshot noise exposure. Other animal studies involving guinea pigs exposed to high level noise demonstrate that the pars inferior (cochlea and saccule) is the most susceptible to damage (Hamernik & Henderson, 1984), while the pars superior (semicircular canals and utricle) remains free of damage (McCabe & Lawrence, 1958). This differential sensitivity is attributable to the existence of the membrane limitans which serves as a barrier between the pars superior and inferior (Hara & Kimura, 1993).…”
Section: Impact On Hearing After Long Term Exposure To Gunshot Noisementioning
confidence: 94%
“…Early studies showed that the sacculus and the cochlea (pars inferior) can be affected by noise, whereas the utriculus and semicircular canal are not [2,3,13,14] . There is no postmortem study on the sacculus's involvement in NIHL.…”
Section: Discussionmentioning
confidence: 99%
“…The vestibular system, especially sacculus damage caused by noise, emerges by the same mechanism [9,10,13] . the sacculus, inferior vestibular nerve, vestibular nucleus, and cervical muscle activity [3] .…”
Section: Discussionmentioning
confidence: 99%